Legal Analysis of Cohabitation and Adultery Delict in Law No. 1 of 2023 On the Criminal Code - Kaila Intan Fatihah; Ali Masyhar Mursyid (Universitas Negeri Semarang, 2026)
This study examines the criminalization of adultery and cohabitation in Law No. 1 of 2023 on the Criminal Code (KUHP), focusing on the effectiveness of the absolute nature of the delict under Articles 411 and 412. The main problem identified is the restriction of the subject of the complaint to only include the immediate family, thus creating a legal impasse in accommodating living law, as well as the communal community's unrest over violations of decency in their neighborhood. The purpose of this study is to formulate an ideal formulation of more adaptive law enforcement through normative legal research methods with a legislative and conceptual approach. The results of this study indicate that restricting the right to complain risks triggering vigilante justice (eigenrichting), thus requiring a reorientation of the paradigm through the reconstruction of the nature of the delict into a relative complaint delict. In conclusion, this study offers an ideal formulation in the form of expanding the legitimacy of complainants to include four main pillars, namely husband or wife, parents, children, and traditional leaders or community leaders. This mechanism for making complaints has included traditional authority as a way of moderating the role of social filter in protecting individual privacy and family integrity, yet achieving a balance with the need to maintain socio-cultural peace through local culture and ethics of the Indonesian nation as well as to create a situation where complaint mechanisms are used only as a last resort (the principle of ultimum remedium).